Efektifitas Pembelajaran E-learning Berbasis Sosial Media pada Anak di Masa Pandemi Covid-19 - Dela Saputri Adam; Andi Arniyanti; Erna Kasim; Nurbaiti Nurbaiti (Universitas Batanghari Jambi, 2022)
Covid-19 (Corona Virus Disease 19) is an outbreak of a disease originating from a new type of virus that was first discovered in Wuhan, China in December 2019 and has never been previously identified to attack human.the government issued new rules such as learning from home which is carried out using the e-learning method. This research (literature review) aims to find out the effectiveness of social media-based e-learning learning for children during the 19th pandemic. This study explores quantitative evidence published in electronic database such as Proquest and Google Sholar. By using a journal search strategy, the results were 4 articles that became the main references in the preparation of this research. Author can see a significant effect of e-learning on children during the covid-19 pandemic. Based on the results of research from the literature review, it can be concluded that e-learning learning for PAUD and elementary school age children is less effective, judging from the teachers and parents of students who say that children experience a decline in learning. It is hoped that in the future there will be a more effective and effecient online learning model that can be accepted by children, teachers and parents during this pandemic.